Microbial Fuel Cells Powered by Tempeh Wastewater: Electricity Generation and COD Removal - Alfiah Alif (Science Journal Get Press, 2026)
Tempeh, a traditional fermented soybean food product widely consumed in Indonesia and Southeast Asia, is produced through a solid-state fermentation process using Rhizopus oligosporus mold. Its production generates large volumes of organic-rich wastewater with Chemical Oxygen Demand (COD) reaching up to 5,000 mg/L, posing significant environmental challenges if discharged without treatment. This study investigates the application of Microbial Fuel Cells (MFCs) to simultaneously treat tempeh wastewater and generate bioelectricity. Three MFC configurations were evaluated: single-chamber, double-chamber (with Nafion 117 proton exchange membrane), and stacked systems, inoculated with mixed microbial consortia enriched from tempeh wastewater sludge. The stacked MFC achieved the highest electricity generation performance, with a maximum open-circuit voltage of 1,248.6 ± 28.3 mV and a maximum power density of 498.2 ± 19.6 mW/m², alongside the highest COD removal efficiency of 88.9 ± 2.1% and Coulombic Efficiency of 31.4%. Electrochemical characterization confirmed effective biofilm formation and electron transfer, while microbial community analysis identified Geobacter sulfurreducens and Pseudomonas aeruginosa as dominant exoelectrogenic species. These results demonstrate that MFC technology powered by tempeh wastewater offers a promising green approach for simultaneous wastewater treatment and energy recovery in food processing industries.